ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN PADA PT. TOYODA GOSEI SAFETY SYSTEMS INDONESIA - Sri Agustini; Laras Agustini (Sekolah Tinggi Ilmu Ekonomi Gici, 2021)
Payroll accounting systems are designed to handle employee salary transactions and their payments. The formulation of the problem studied is how the payroll accounting information system at PT. Toyoda Gosei Safety Systems Indonesia. The purpose of this study is to determine the description of payroll systems and procedures and their implementation in fulfilling the elements and objectives of internal control of the payroll system at PT. Toyoda Gosei Safety Systems Indonesia. This research took the object of research at PT. Toyoda Gosei Safety Systems Indonesia. The method used by the author is the evaluative descriptive method. The data used by the author are primary data and secondary data. The data collection techniques used are observation, interviews and literature studies. The results showed that the implementation of payroll systems and procedures of PT. Toyoda Gosei Safety Systems Indonesia in fulfilling the elements and objectives of internal control payroll system is still ineffective. This is characterized by the existence of a schedule of duties from the procedure of making payrolls and wages as well as making payments of salaries and wages, the entry of clock cards into unsupervised timekeeping machines, payrolls and wages and salary deductions not authorized by the staffing department.